Сompanions of (n1, n2)-Jonsson theory - Yeshkeyev, A.R.; Omarova, M.T. (Bulletin of the Karaganda University. Mathematics Series, 2019)
In given work are considered model - theoretical properties of companions of (n1; n2) - Jonsson theory. Also were considered a communications between center and (n1; n2) - Jonsson theory. Herewith considered theories is perfect in the sense of the existence of appropriate model companion. In given article introduced new concepts: (n1; n2) - Jonsson theory, D - model companion. New results are shown with respect to model companions of - Jonsson theory and 1 - perfect 1 - Jonsson theory.